Manutenção preventiva em sistemas de ar comprimido: estudo de caso GKN do Brasil - filial Porto Alegre - RS - Bykowski, Francisco (Universidade do Vale do Rio dos Sinos, 2014)
As an important part of business, the maintenance ensures effectiveness of industrial production in large scale and correct use and scaling maintenance techniques to guaranty the excellence and reliability to equipment and facilities. Energy efficiency and environmental conservation are directly related with maintenance. This article discusses preventive maintenance techniques to facilities, and waste of electricity related with leaks in a compressed air system on GKN Brazil Facilities, Justifying an investment to correct related problems in compresses air system.
Keywords: Manutenção preventiva; Ar comprimido; Eficiência; Energia; Preventive maintenance; Compressed air; Efficiency; Energy